Development of hybrid land use change model for compact city assessment - Abdullahi, Saleh (2016)
In recent decades, attaining urban sustainability is one of the most primary goals for planners and decision makers in urban related applications. Rapid population growth and rural to urban migration increase the conversion of valuable natural environments to build up areas, and produce several environmental, economic and social issues. Among various aspects of urban sustainability, environmental protection especially agricultural and forest conservations are dominated in tropical countries like Malaysia. Hence, it is important to propose various alternative development scenarios based on objectives of urban sustainability to avoid negative consequences of urban sprawl developments. Compact city is widely accepted as one of the most promising solution for urban development pattern. Compact urban development aims to protect natural environment, reduce land consumption, decrease car dependency, support public transportation facilities, and so on. This study as the first objective discovered the spatiotemporal of urban land use change patterns to highlight the trend of historical development of Kajang City (Malaysia) during years 2004 to 2015. In the second objective, as an initial step of compact city modeling, comprehensive compactness assessment were proposed and implemented based on urban density, intensity and land use diversity. Next, by considering the degree of compactness (DoC) of temporal land use maps, trend of compactness (ToC) of the study area were extracted and evaluated which reveal the growth pattern of compactness. Third objective deals with projection of future development pattern (business as usual scenario) based on several urban related factors and interaction among various land use categories through a novel hybrid cellular and statistical-based integration approach. In this hybrid model,statistical methods such as Weights-of-Evidence (WoE) and Markov Chain were used to evaluate the probability of growth of Kajang City land use types. Next, the results were integrated to Cellular automata (CA) model to facilitate the application of contiguity filters and project the future land use maps based on neighbourhood concept. Finally, by considering the proposed land use modeling approach and evaluation of DoC and ToC, a compact land use scenario were proposed and implemented using city intensification process. Kajang City is selected as case study, because this city in recent years has faced rapid urbanization and large sprawl developments due to its proximity to three main cities of Malaysia. In addition, availability of large proportion of natural environments in this region caused an adequate observation of the effects of urban growth. Although there are many abandoned plots and brownfield sites exist within the municipality, most of the current growth and developments are occurring at the outskirts and through rural environments. Therefore, this study attempts to analyse and model compact development to provide an alternative solution instead of current development patterns of this city. In general, this study utilized geospatial data within GIS environment to analyse the urban growth process and its pattern with respect to compact city paradigm. According to evaluation of historical land use growth pattern of the study area, it was observed that this city had significant growth and changes during years 2004 to 2012, but few changes have occurred in last three years. Residential, commercial and industrial land use categories had the main growth, and agricultural and open spaces had the main loss during the selected period of time. However, compactness assessment process indicated a gradual growth of DoC of Kajang City which in fact should be enhanced to achieve sustainable environment. This aim was achieved, by evaluating city compactness of both proposed land use scenarios for year 2026, in which the DoC of compact land use scenario was higher than business as usual scenario. Results confirmed that the proposed modeling approaches, geospatial data, statistical techniques and GIS are very practical for identifying urban growth and land use change patterns and their general trends in future. The analyses and modeling approaches used in this study can be employed to guide the identification and measurements of the changes and growth likely to happen in urban areas.